Sustainable Environmental Management Through a Municipal Solid Waste Charging Scheme: A Hong Kong Perspective - Cheng, Cuicui; Zhou, You; Zhang, Lin (Frontiers in Environmental Science, 2022)
Municipal solid waste (MSW) charging is a method of waste management that involves charging residents for garbage disposal. Due to the increasing levels of MSW, Hong Kong has planned to implement an MSW charging scheme in 2023. This article evaluates the potential efficacy and challenges of an MSW charging scheme in Hong Kong. We first summarize the experiences from Taipei and Seoul, which are two typical cities that have successfully implemented the charging scheme to handle MSW. Strong enforcement and good supportive resources in the two cities have resulted in highly effective MSW management. We then provide an IPAT analysis of the urgency of Hong Kong’s MSW concerns and a PEST analysis of the readiness of Hong Kong to implement MSW charging. We highlight the challenges with actionable suggestions for sustainable environmental management.